2011
DOI: 10.1074/jbc.m111.237065
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipogenesis and Stearate Accelerate Vascular Calcification in Calcifying Vascular Cells

Abstract: Vascular calcification is recognized as an independent predictor of cardiovascular mortality, particularly in subjects with chronic kidney disease. However, the pathways by which dysregulation of lipid and mineral metabolism simultaneously occur in this particular population remain unclear. We have shown that activation of the farnesoid X receptor (FXR) blocks mineralization of bovine calcifying vascular cells (CVCs) and in ApoE knock-out mice with 5/6 nephrectomy. In contrast to FXR, this study showed that li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 48 publications
3
52
1
Order By: Relevance
“…For phosphorylated (p-)ATF4 detection, the promoted mineralization of VSMCs compared with other fatty acids. Inhibition of acetyl-CoA carboxylase or acyl-CoA synthetase reduced mineralization of VSMCs, whereas inhibition of stearoyl-CoA desaturase (which converts stearate to oleate) promoted mineralization and osteoblastic differentiation ( 12 ). We also found that increased cholesterol synthesis and uptake by LXR and SREBP-1c activations contributed to vascular calcifi cation ( 13 ).…”
Section: Western Blottingmentioning
confidence: 53%
See 4 more Smart Citations
“…For phosphorylated (p-)ATF4 detection, the promoted mineralization of VSMCs compared with other fatty acids. Inhibition of acetyl-CoA carboxylase or acyl-CoA synthetase reduced mineralization of VSMCs, whereas inhibition of stearoyl-CoA desaturase (which converts stearate to oleate) promoted mineralization and osteoblastic differentiation ( 12 ). We also found that increased cholesterol synthesis and uptake by LXR and SREBP-1c activations contributed to vascular calcifi cation ( 13 ).…”
Section: Western Blottingmentioning
confidence: 53%
“…There are four reasons for using MOVAS-1 cells in this study, instead of the primary bovine calcifying vascular cells used in our previous studies ( 11,12 ). First, MOVAS-1 cells have been established as a cell culture model of vascular calcifi cation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations